Comparison of unsaturated behaviour of residual soil in Malaysia and the effect of particle size distribution - Suleiman Haji Nassor; Siti Jahara Matlan; Nazaruddin Abd Taha; Aniza Ibrahim; Rohaya Alias; Muhammad Mukhlisin (Semarak Ilmu Publishing, 2025)
The unsaturated behaviour of residual soil in Malaysia has been studied, yet the impact of particle size distribution (PSD) on soil-water characteristics still needs to be more adequately explored. Previous research highlights the significance of fine particles in controlling geotechnical properties. This study investigates how the PSD of five soil samples influences the Soil-Water Characteristic Curve (SWCC) parameters, water retention, storage properties and permeability. The study involved five samples, four samples from Ibrahim et al., [1] research, such as reserved forest, gravelly sand, silty sand, kaolin and silty clay soil from the Garinono Formation soil. A pressure plate extractor determined the samples' Soil-Water Characteristic Curve (SWCC) and bulk density. The van Genutchen (1980) model fitted experimental data and the hydraulic response was studied on the five soil samples. The results show that Kaolin and silty clay have higher volumetric water content than gravelly and silty sand due to a higher percentage of silty and clay particles. However, the reserve forest sample has volumetric water content like kaolin and silty clay due to its natural location. Reserved forest, kaolin and silty clay samples have higher water storage, i.e., effective soil porosity (ESP) values than gravelly sand due to higher clay and silty contents. Silty sand, reserve forest and gravelly sand have higher shape parameter (n) values due to their higher sand and gravel content. Clay-rich samples had smaller (n) values, indicating a more uniform distribution. Hydraulic conductivity function (K(θ)) is influenced by scale parameter (α), Air-Entry Value (AEV) and Saturated Hydraulic Conductivity K_s. Kaolin and silty clay samples exhibit lower α values, resulting in higher suction at AEV than other soils as they contain high silty and clay contents. Saturated conductivity values directly affect hydraulic conductivity function, while AEV inversely affects the unsaturated flow. Understanding unsaturated hydraulic responses and SWCC characteristics could assist in anticipating slope instability and ground stabilisation in residual soil and soil behaviour during and after rainfall.